Symptom management practice of 232 patients with liver malignant tumors undergoing radiofrequency ablation based on symptom evaluation by using MDASI-TCM (基于MDASI-TCM的232例肝脏恶性肿瘤射频消融患者的症状管理实践) - ZHANG Ying (张莹); KANG Dongqin (亢东琴); WANG Yun (王云); SUN Hong (孙红) (中西医结合护理)
Objective To summarize the incidence, degree and practical experience of symptom management of 232 patients with liver malignant tumors after ultrasound-guided radiofrequency ablation. Methods Totally 232 patients with liver malignant tumors were evaluated with the MD Anderson Symptom Inventory for Traditional Chinese Medicine (MDASI-TCM). The screened symptoms were systematically intervened and managed according to the established symptom management process, and the effect of intervention based on MDASI-TCM assessment was evaluated before discharge. Results The top five common symptoms of patients after radiofrequency ablation were pain (58. 19%), fatigue (51. 29%), nausea (47. 41%), sleep (42. 24%), distress (38. 79%). The degree of symptoms was mainly mild, which could interfere with the patients' life to a certain extent. After targeted symptom management intervention for patients undergoing radiofrequency ablation of liver tumor, the incidence and degree of symptoms and interference to life were significantly improved. Conclusion Evaluation of patients' symptoms and degree after ultrasound-guided liver radiofrequency ablation is helpful for medical staff to quickly and comprehensively grasp the general situation of patients, manage the symptoms in the whole process, and provide targeted health guidance, so as to improve the symptoms after ultrasound-guided radiofrequency ablation, decrease the disturbance of patients’ life, improve the quality of life of patients during perioperative period, and reduce the incidence of adverse reactions, It is conducive to the patient's recovery as soon as possible. (目的 总结232例肝脏恶性肿瘤患者行超声引导下射频消融术后常见症状的发生率、程度及症状管理的实践经验。方法 应用肿瘤常见症状及中医症状调查量表(MDASI-TCM)对科室2018年7月—2022年11月收治的232例肝脏恶性肿瘤患者在射频消融术后进行评估, 对筛查出的症状按照科室制订的症状管理流程系统地有针对性的进行干预和管理, 在出院前对患者再次采用MDASI-TCM进行症状管理的效果评价。结果 肝射频消融术后患者常见症状发生率前五位依次为疼痛(58. 19%)、疲乏(51. 29%)、恶心(47. 41%)、睡眠(42. 24%)、苦恼(38. 79%), 症状程度以轻度为主, 会对患者产生一定程度的生活干扰; 根据症状管理流程对肝脏肿瘤射频消融患者进行有针对性的症状管理干预后, 患者症状发生率、程度及对生活的干扰均明显改善。结论 超声引导下肝射频消融治疗后对患者症状及程度进行及时评估有利于医护人员快速、全面掌握患者一般状况, 对筛查出的症状进行规范的全程化管理, 并有针对性的进行健康指导, 能有效地改善患者术后症状, 减少对患者生活的干扰, 提高患者围手术期的生活质量, 降低不良反应的发生率, 有利于患者术后身体的尽快康复。)